Tinjauan Kuat Geser Balok Beton Dengan Tulangan Model Rangka Dari Kayu Meranti - Saputro, Eka Fitri; Ir. H. Aliem Sudjatmiko, M.T (2016)
Concrete is a construction material that is now commonly used and is a building material that has been chosen by experts of the structure. The amount of concrete due to the use of concrete made from materials that are easy to obtain, processed, treated, formed, the price is relatively cheap and has a high compressive strength. Reinforced concrete is a construction that is not foreign in the field of civil engineering. reinforced concrete structure is designed to be able to receive the internal forces, which form the normal force, bending moments, torsion moments, and styles latitude / shear. With the internal forces, will provide resistance of structural elements in the form of normal stress, bending stress, stress torsion and shear stress. Shear strength is also influenced by the shear reinforcement that is attached, in the form of shear reinforcement stirrups or slant / oblique. Reinforcement of meranti wood frame models in this study were selected because of the type of reinforcement is considered suitable models and is expected to add to the shear strength on concrete beams. Reasons for meranti wood on the building because it is easy to come by, have a high aesthetic value and are cheaper when compared to teak. Meranti wood used as a substitute for iron reinforcement using wood lath size 2/3, Reinforcement lengthwise using plain reinforcement diameter (dp) 8 mm, Reinforcement begel using plain reinforcement diameter (dp) 4 mm. Test specimen in the form of a beam with a size of 20 cm x 30 cm x 60 cm with 4 pieces. Concrete testing done after 28 days. The test includes testing the compressive strength of concrete. Tests conducted to determine the compressive strength of concrete cylinder compressive strength, then load testing to determine the shear strength of reinforced concrete beams with spaces begel 8 cm and 10 cm. The results of testing the strength of concrete cylinders obtained an average of 18.96 MPa compressive strength. The test results loading concrete beams obtained shear force par for concrete beams with steel reinforcement spacing begel 8 cm 85.06 kN and spaced begel 10cm 78.13 kN, while the concrete beams with reinforcement of the model order of meranti spaces begel 8 cm 81.13 kN and for space begel 10 cm 75.00 kN. The difference between the nominal shear force concrete beam using steel reinforcement and reinforcement of meranti wood frame models for space begel 8 cm is 3.93 kN or 4.61% and spaced 10 cm begel is 3:13 kN or 3.99%.